The Effect of Measurement Errors on the Synthetic x̄ Chart. (26th August 2014) - Hu, XueLong; Castagliola, Philippe; Sun, Jinsheng; Khoo, Michael B.C.
Abstract : Measurement errors often exist in quality control applications. In this paper, the performance of the synthetic X ̄ chart is investigated when measurement errors exist using a linearly covariate error model. It is shown that the performance of the synthetic X ̄ chart is significantly affected in the presence of measurement errors. The effect of taking multiple measurements for each item in a subgroup on the performance of synthetic X ̄ chart is also investigated in this paper. An example is provided in order to illustrate the application of the synthetic X ̄ chart with measurement errors. Copyright © 2014 John Wiley & Sons, Ltd.